Research Progress on Mitochondrial Dysfunction in Diabetic Retinopathy - Yiwei Wu; Haidong Zou (MDPI AG, 2022)
Diabetic Retinopathy (DR) is one of the most important microvascular complications of diabetes mellitus, which can lead to blindness in severe cases. Mitochondria are energy-producing organelles in eukaryotic cells, which participate in metabolism and signal transduction, and regulate cell growth, differentiation, aging, and death. Metabolic changes of retinal cells and epigenetic changes of mitochondria-related genes under high glucose can lead to mitochondrial dysfunction and induce mitochondrial pathway apoptosis. In addition, mitophagy and mitochondrial dynamics also change adaptively. These mechanisms may be related to the occurrence and progression of DR, and also provide valuable clues for the prevention and treatment of DR. This article reviews the mechanism of DR induced by mitochondrial dysfunction, and the prospects for related treatment.